Mitral Valve Surgery for Persistent or Recurrent Mitral Regurgitation After Transcatheter Edge‐to‐Edge Repair Is Associated With Improved Survival - Ahmed El Shaer; Alejandra Chavez Ponce; Piotr Mazur; Kevin Greason; Arman Arghami; Mackram F. Eleid; Mayra Guerrero; Charanjit S. Rihal; Juan A. Crestanello; Mohamad Alkhouli (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background The management of severe mitral regurgitation (MR) after transcatheter edge‐to‐edge repair (TEER) remains a clinical conundrum. Considering the growing volume of TEER, more outcomes data for mitral surgery in this cohort are needed. Methods and Results Symptomatic patients with persistent or recurrent severe MR after TEER evaluated between May 2014 and June 2021 were included. The primary outcome was all‐cause mortality in patients who were treated with surgery versus medical therapy. The Kaplan–Meier and Cox regression methods were used to report risk‐adjusted survival analyses. Among the 142 included patients, 44 (31.0%) underwent mitral surgery. Patients who underwent surgery were younger than those treated medically (74.1±8.9 versus 78.6±10.5 years, P=0.01). Major comorbidities were similar except obesity, sleep apnea, left ventricular dimensions, and ejection fraction. Society of Thoracic Surgeons Predicted Risk of Operative Mortality was 9.0±4.7 versus 7.9±4.9 in the surgical versus medical therapy groups, respectively, P=0.22. Time from TEER to detection of severe MR was similar in both groups (median [interquartile range] 97.5 [39.5–384] versus 93.5 [40–389] days in the surgical versus medical groups, respectively [P>0.05]). In the surgical group, valve replacement was performed in all patients. Operative mortality was 4.5% (observed/expected ratio 0.55), and major complications were uncommon. After risk‐adjustment, surgery was associated with significantly lower all‐cause mortality (adjusted hazard ratio, 0.33 [95% CI, 0.12–0.92], P=0.001) compared with medial therapy. Conclusions Compared with medical therapy, mitral surgery in patients with severe persistent or recurrent MR after TEER is associated with lower mortality despite the high‐risk profile of these patients. Patients with severe MR after TEER should be considered for surgery at a referral mitral surgical center.